2015
DOI: 10.9734/jsrr/2015/11339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stages of Enrichment on the Chemical Composition of Soy-melon “Gari”– A Protein Enriched Cassava Semolina

Abstract: Aims:This study aimed at determining the effects of enriching "gari", a fermented, dewatered and toasted granules from cassava with soy-melon, a legume protein supplement on its chemical composition. Study Design:The study was carried out under a Randomized Complete Bloch design using ANOVA to analyze the replicate data obtained while Duncan New Multiple Range (DNMR) test was used to separate the means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
5
4
1
Order By: Relevance
“…The observed increase in the protein content of the sample substituted with 50% soybean flour could be attributed to the addition of high proportion of soybean flour to the blend. The increase in protein content of the sample is in agreement with the report of Oluwamukomi and Adeyemi [19] for poundo yam enriched with defatted soybean flour. The high protein contents of soy-poundo yam composite blends produced in this study would be of great importance in reducing the protein-energy malnutrition resulting from high cost of conventional animal products particularly in less developed and developing countries of the world including Nigeria.…”
Section: Proximate Composition Of Soy -Poundo Yam Composite Blendssupporting
confidence: 91%
See 1 more Smart Citation
“…The observed increase in the protein content of the sample substituted with 50% soybean flour could be attributed to the addition of high proportion of soybean flour to the blend. The increase in protein content of the sample is in agreement with the report of Oluwamukomi and Adeyemi [19] for poundo yam enriched with defatted soybean flour. The high protein contents of soy-poundo yam composite blends produced in this study would be of great importance in reducing the protein-energy malnutrition resulting from high cost of conventional animal products particularly in less developed and developing countries of the world including Nigeria.…”
Section: Proximate Composition Of Soy -Poundo Yam Composite Blendssupporting
confidence: 91%
“…The ascorbic acid contents of the soy-poundo yam composite blends were generally higher than that of the control (100% instant yam flour), and this is an indication that soybeans are a good source of ascorbic acid [29]. Similar increase in ascorbic acid content was reported by Oluwamukomi and Adeyemi [19] for poundo yam enriched with defatted soybean flour. Vitamin C which is a water-soluble vitamin plays a vital role in the body building process and in disease prevention [37].…”
Section: Vitamin Composition Of Soy-poundo Yam Composite Blendssupporting
confidence: 79%
“…The samples show significant difference (p<0.05). These values compared well with values recorded for crude fibre content of soymelon gari obtained by Oluwamukomi et al, (2007) who reported 2.40 to 6.80 % but higher than the value (2.00 to 2.16 %) and (1.73 to 2.11 %) reported by Ogunlakin et al, (2015) for soy-gari and Karim et al, (2015) respectively. Fibres aid in digestive processes lowers the vitamin and enzyme content of the food material (Alaise & Linden, 1999).…”
Section: Proximate Composition Of Cowpea Hull-enriched Garisupporting
confidence: 87%
“…The result obtained in this study is slightly higher than (4.04 to 4.67 mg/100g) recorded by Owuno et al, (2021) for gari fermented with maize residue. But, lower than 49.62 to 69.54 mg/100g and 16.20 to 18.62 mg/100g for soy-gari and Soy-melon enriched gari respectively (Ogunlakin et al, 2015;Oluwamukomi & Adeyemi, 2015). The low phosphorus content recorded in this study might be due to the fact that the cowpea hulls are used in this study compare to full whole grains used by other authors and the phosphorus content in soybean is also high than cowpea.…”
Section: Proximate Composition Of Cowpea Hull-enriched Garimentioning
confidence: 52%
See 1 more Smart Citation